A comprehensive review on effect of cold metal transfer welding parameters on dissimilar and similar metal welding - Singh, Indra Jeet; Murtaza, Qasim; kumar, Paras (Maǧallaẗ al-abḥath al-handasiyyaẗ, 2025)
Cold Metal Transfer (CMT), an advanced technology developed from the conventional metal inert gas (MIG) process, has revolutionized the joining of similar and dissimilar metals due to low heat input. The authors analyzed the physics of welding involved in the process, the metallurgical effect on the alloys, and different mechanical and corrosion properties due to variations in the parameters involved during welding. The shielding gas/es effect is studied to understand the bead modification in different environments and its impact on mechanical properties. Moreover, comparing the modified technique to the conventional method showed considerable improvement in weld defects, the heat-affected zone (HAZ) width, and the weld finish on the surface. An analysis of the heat input model and heat input calculation is also carried out to ease the study of the simulation of the CMT process. These analyses had drawn some critical research gaps in the research conducted in the past, which the upcoming researchers in this field can address.